Shallow-layer earth temperature energy managing system - TENG YANJING; CHEN QIANXIN; TAO YUEZAN (2017)
The invention discloses a shallow-layer earth temperature energy managing system. The shallow-layer earth temperature energy managing system comprises an energy datum collecting unit, a datum warehouse storing unit and a datum mining analyzing unit. Therefore, efficient and stable automatic operation is achieved, automatic monitoring and managing are achieved for a central air-conditioning system, damage possibly caused to the air-conditioning system due to human factors is avoided or reduced, stability of operation of the central air-conditioning system is improved, and thus indirect economic benefits are created; and linkage control over units such as a unit, a chilled water pump and a cold source water pump can be completed, and thus optimum operation of the system can be further achieved. 本发明公开种浅层地温能能源管理系统，其中，浅层地温能能源管理系统包括：能源数据采集单元、数据仓库存储单元和数据挖掘分析单元。从而实现高效稳定的自动化运行，并对中央空调系统实现自动化的监测和管理，避免或减少了由于人为因素而可能造成的对空调系统的伤害，提高了中央空调系统运行的稳定性，从而创造了间接的经济效益；并可完成对机组，冷冻水泵，冷源水泵等单元的联动控制，从而进步实现了系统的优化运行。